2021
DOI: 10.1021/acsinfecdis.0c00797
|View full text |Cite
|
Sign up to set email alerts
|

New Antimicrobial Peptides with Repeating Unit against Multidrug-Resistant Bacteria

Abstract: With the aim of tackling the increasingly serious antimicrobial resistance and improving the clinical potential of AMPs, a facile de novo strategy was adopted in this study, and a series of new peptides comprising repeating unit (WRX) n (X represents I, L, F, W, and K; n = 2, 3, 4, or 5) and amidation at C-terminus were designed. Most of the newly designed peptides exhibited a broad range of excellent antimicrobial activities against various bacteria, especially difficult-to-kill multidrug-resistant bacteria c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 56 publications
(97 reference statements)
0
30
0
Order By: Relevance
“…Studies have shown that sodium ions, calcium ions, and other divalent ions can disturb the electrostatic interaction between AMPs and bacterial membranes through electrostatic shielding, resulting in a reduction in bacteriostatic effects. 47 In addition, divalent ions, such as calcium ions, can also competitively bind to LPS on the outer membrane of Gram-negative bacteria to reduce the antibacterial activity of AMPs. 42 This notion explains why the antibacterial effect of AMPs will decrease in the environment of ions, such as Na + , Ca 2+ , Mg 2+ , and so forth.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that sodium ions, calcium ions, and other divalent ions can disturb the electrostatic interaction between AMPs and bacterial membranes through electrostatic shielding, resulting in a reduction in bacteriostatic effects. 47 In addition, divalent ions, such as calcium ions, can also competitively bind to LPS on the outer membrane of Gram-negative bacteria to reduce the antibacterial activity of AMPs. 42 This notion explains why the antibacterial effect of AMPs will decrease in the environment of ions, such as Na + , Ca 2+ , Mg 2+ , and so forth.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Next, we tested the changes in the antibacterial ability of synthetic peptides at different physiological salt concentrations. Studies have shown that sodium ions, calcium ions, and other divalent ions can disturb the electrostatic interaction between AMPs and bacterial membranes through electrostatic shielding, resulting in a reduction in bacteriostatic effects . In addition, divalent ions, such as calcium ions, can also competitively bind to LPS on the outer membrane of Gram-negative bacteria to reduce the antibacterial activity of AMPs .…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, [ 30 ] K 4 and K 5 showed high antibacterial activity and low toxicity, with ideal antibacterial potential. Thus, we chose K 4 or K 5 as an adjuvant in this study, to further explore their potential in eliminating or reversing the resistance of Gram‐negative bacteria when combining them with the traditional antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…For some strains, K 5 showed better antimicrobial activity than K 4 , which may be due to its stronger α‐helix tendency, which was consistent with the previous research of our group. [ 30 ] Among all the strains tested, the antimicrobial activity of four traditional antibiotics was ranked as ciprofloxacin, rifampicin, gentamicin, and imipenem. And the vast majority showed lower antimicrobial activity against the obtained antibiotics‐resistant bacteria than the standard strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation